1999
DOI: 10.1177/003435529904300107
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Dilemmas Related to Counseling Clients Living with HIV/AIDS

Abstract: This study tested an eight-factor model of client actions/decisions in terms of the extent to which professionals counseling persons with HIV/AIDS believed that those actions/decisions presented ethical dilemmas, and the frequency with which they encountered such actions. A confirmatory factor analysis lent initial support for the hypothetical eight-factor ethical-dilemma model for the ratings regarding the extent to which the participants believed those items constituted ethical dilemmas. Similar results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, a point can be made about its potential applicability in a variety of settings. Garcia et al (1999) conducted a confirmatory factor analysis study that showed the complexity of ethical dilemmas faced by counselors working with HIV/AIDS populations. They found that counselor ratings of the dilemmas loaded onto eight categories, namely, disclosure, family/social, legal, health, death, vocational, sexual, and counselor/client relationship issues.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…However, a point can be made about its potential applicability in a variety of settings. Garcia et al (1999) conducted a confirmatory factor analysis study that showed the complexity of ethical dilemmas faced by counselors working with HIV/AIDS populations. They found that counselor ratings of the dilemmas loaded onto eight categories, namely, disclosure, family/social, legal, health, death, vocational, sexual, and counselor/client relationship issues.…”
Section: Potential Applicationsmentioning
confidence: 99%